18 Higher mortality in normal weight heart failure patients is unexplained by differences in gender, age, ventricular function or drug treatment. (28th September 2016) - Pharithi, R; Carey, M; Fall, S; Khan, B; Egom, E; Moore, D; Maher, V; Starr, N
Abstract : Background: Despite lack of strong evidence that weight loss in patients with chronic heart failure result in overall improved survival, the current guidelines still recommend loss of weight loss in patients with increased adiposity. Mortality is higher in normal weight patients with chronic heart failure (CHF) compared to their overweight and obese counterparts. It is still unknown if conventional risk factors account for this mortality difference. Purpose: We investigated if age, gender, cardiomyopathy type, left ventricular dimensions or function, functional capacity, or drugs used could explain this mortality differences in relation to euvolaemic body mass index (BMI). Methods: Retrospective review of 329 patients followed in the HF programme over the last 12 years. Patient data was recorded when they were stabilised on appropriate treatment. Results: In this long term follow up study mortality was higher in patients with normal weight compared to overweight and obese patients. This differences was unexplained by differences in age, gender, disease type, ventricular size or function. Patients with increased BMI were more hypertensive (p < 0.001) and had higher prevalence of dyslipidaemia (p = 0.031). In addition, no significant differences in treatment or weight during follow up were observed. See Table 1 and Figure 1 which show risks of All-cause of mortality and survival curves respectively. Conclusion: Our data highlights that having a lower BMI has adverse effect on survival in patients with HF. However, there was no obvious risk factors that could account for this mortality differences. Future studies need to examine which specific obesity related factors reduce their mortality risk.